Clonal multiplication of carnation by micropropagation - Davis, Michael Jay, author; Baker, Ralph R., advisor; Nabors, Murray W., committee member; Hanan, Joe J., committee member (Colorado State University. Libraries, 1975)
Clonal multiplication of carnation (Dianthus caryophyllus L.) was accomplished in three stages: (1) shoot tip culture initiation, (2) shoot multiplication , and (3) rooting stages . Shoot tips approximately 1 mm in height, as used in the micropropagation of pathogen-free plants, were grown on a modified Murashige and Skoog medium with 10 μM kinetin and 1 μM NAA. This solidified medium supported rapid growth of morphologically normal shoots, while counteracting apical dominance. It was selected after comparing various inorganic salt mixtures, vitamin mixtures , carbohydrates, growth regulators , and additional supplements for their effect on shoot tip growth. After 3 to 4 wk in the initiation stage, proliferated shoot tip cultures were transferred to the multiplication stage. They were each grown in separate flasks containing the same medium as in the previous stage but without agar and with one fourth the concentration of NAA and kinetin. The flasks were attached to an auxophyton and revolved horizontally at 1 rpm. Growth of axillary shoots was enhanced in this stage , and shoot tip cultures, usually with two or three shoots over 2 cm in length at the beginning of this stage, consistently produced more than 10 shoots of similar length in another 3 wk. Plantlets were obtained by rooting the individual shoots from the multiplication stage. In the rooting stage conventional techniques for rooting carnation cuttings were applicable. BR-8 synthetic soil blocks and Jiffy-7 expandable peat pellets were used as supports for root initiation and development. These rooting supports increased survival of plantlets over other types of media conventionally used in propagation. Micropropagation by the method developed in this research produced some abnormal plants, and selection for plants with desired characteristics may be necessary. Incorporation of this method into a pathogen-free stock program might prove beneficial if large scale use of it is limited by economic considerations.
Keywords: Carnations